2016
DOI: 10.1111/sms.12777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12‐week resistance training during radiotherapy in breast cancer patients

Abstract: Exercise is considered to be an effective supportive treatment approach in breast cancer (BC) patients. We conducted a randomized controlled trial to assess the efficacy of a 12-week PRT during radiotherapy. Strength performance was assessed by maximal isokinetic peak torque (MIPT) in two different angular velocities (60°/s and 180°/s) and maximal voluntary isometric contraction for shoulder external and internal rotation, as well as for knee extension and flexion were assessed pre- and post-intervention in 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 42 publications
1
38
0
1
Order By: Relevance
“…These 41 articles were derived from a total of 16 trials ( Table 4 ) [ 7 , 8 , 10 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The BEATE study [ 26 , 27 ] and the BEST study [ 8 , 28 , 29 , 30 ] were treated as a single trial in the present review because they shared the same training program. The PAL [ 46 , 47 , 48 , 49 , 50 , 51 , 52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 41 articles were derived from a total of 16 trials ( Table 4 ) [ 7 , 8 , 10 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The BEATE study [ 26 , 27 ] and the BEST study [ 8 , 28 , 29 , 30 ] were treated as a single trial in the present review because they shared the same training program. The PAL [ 46 , 47 , 48 , 49 , 50 , 51 , 52 …”
Section: Resultsmentioning
confidence: 99%
“…Eleven trials utilized a moderate intensity, between 50% and 80% of 1RM or equal to 8–19 RM [ 7 , 20 , 26 , 31 , 32 , 35 , 39 , 40 , 45 , 46 , 56 ]. Five trials used a high intensity, greater than 80% of 1RM or equal to 5–7 RM [ 20 , 30 , 35 , 46 , 56 ]. One trial used the rated perceived exertion (RPE) scale [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The BEATE and BEST studies have previously shown that after a chemotherapy patients' cardiorespiratory fitness and muscle strength is substantially reduced [20,28], and that a resistance training concomitant to adjuvant therapy can improve muscle strength or ameliorate its therapy-associated decline [29], has beneficial effects on patient-reported outcomes such as fatigue and pain [14,15], and to some extent on inflammatory processes [30]. Therefore, our intervention focusing on well performed progressive resistance exercise training appears important and effective with respect to physiological and psychological factors, but it should be improved with respect to long-lasting physical activity behavior to maintain health benefits in the long run.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 25 Despite the knowledge on upper-limb dysfunction, interventions including resistance training or targeting specific impairments like shoulder immobility are less frequent, 6 , 26 especially during treatment. 8 , 27 Most studies during BC radiotherapy focused only on fatigue modulation, mainly via endurance exercises. 28 - 31 However, endurance exercises during radiotherapy appear insufficient to address functional deficits induced by BC treatment.…”
Section: Introductionmentioning
confidence: 99%